Inquisisi Gereja: Noda Hitam Sejarah Barat - Adian Husaini (Universitas Darussalam Gontor, 2013)
As one foothold to create perspective in understanding the growing phase in the politics of the Christian West, is reviewing Inquisition. In fact it was an Institutional Church, in its trace of history incised dark history. Inquisition, is not excessive to say as a real symbol of the violence perpetrated the Christian West against resistances that emerged from society; Either from other faiths, as well as Christians who deemed to have been out the Church’s mainstream. However it should be noted, Inquisition has resulted an infiltration adapted to the field of Islamic Studies. Equipped with study of Western history, emerged perspective that seems to generalize the political history situation both of religion. This is certainly a fatal problematic, where the conceptual different of religions –in this case Islam and Christian- turned into something that was not respected. The identity of religions may not be generalized by one angle polemic. It is important to be held an identification problem exclusively to provide a clear solution indeed. In this case, the church provides one; secularization